Sistema contable para el manejo de los recursos económicos de la compañía de transportes livianos “Señor del Buen Suceso” C.A., de la Parroquia la Asunción, Cantón Chimbo, Provincia Bolívar, año - Romero Borja, Diana Elizabeth. (2011)
Light Transport Company "Lord of Good Fortune" C. A., does not have an accounting system that allows you to control the inflow and outflow of economic resources and establish a clear and transparent what the real economic situation of the same, for this reason it became necessary to make this work research in which we use the methods: comparative historical and descriptive method, techniques for obtaining information such as interview and observation, types of research: descriptive, explanatory and purposeful. The application of the interview was directed towards the three directors, after making a structured observation of Light Transport Company "Lord of Good Fortune" C. A., which provided us with important information such as, lack of knowledge about the management and administration of financial resources of the same, which it was necessary to conduct this research, while proposing the implementation of an accounting system that allows them to properly manage their resources. The proposal consists of the implementation of a model accounting system in the Transport Company "Lord of Good Fortune" C. A. Parish of the Assumption, with its proper accounting policies, chart of accounts, dynamic analysis, book formats, and implementation of accounting system in a period of one month and the results presented in the same period. Implementation of this accounting system will help to record your daily transactions made, as well as providing reliable and timely information that reveals the economic situation of the Company, and so managers can make better decisions and provide financial reports to the Inspectorate of Companies.